The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/ijpor/eds018
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Political Interest and News Media Consumption: A Longitudinal Perspective

Abstract: This longitudinal study investigates whether the impact of political interest-a key motivational factor behind news consumption-on various forms of news consumption has increased over time. The analysis is based on a unique large-scale representative annual survey conducted in Sweden over the years 1986-2010, enabling a comprehensive analysis of citizens' total and specific news consumption across multiple channels and platforms. Results show that news consumption has become more polarized between news-seekers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(206 citation statements)
references
References 25 publications
(40 reference statements)
12
189
0
5
Order By: Relevance
“…As a consequence, several studies have found growing gaps between heavy users and low/nonusers which are attributable largely to different sets of motivations and gratifications sought by people Ksiazek, Malthouse, & Webster, 2010;Strömbäck et al, 2013). It is also likely the case that differences in the demand for political news would vary even more than differences in demand for news in general.…”
Section: Concern 1: Declining Amount Of Political Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, several studies have found growing gaps between heavy users and low/nonusers which are attributable largely to different sets of motivations and gratifications sought by people Ksiazek, Malthouse, & Webster, 2010;Strömbäck et al, 2013). It is also likely the case that differences in the demand for political news would vary even more than differences in demand for news in general.…”
Section: Concern 1: Declining Amount Of Political Newsmentioning
confidence: 99%
“…The core of the concern is that increasing media choice will lead to increasing inequalities in the extent to which people make use of the news media, and that this will result in increasing inequalities in knowledge about politics and current affairs among different groups in society Blekesaune et al, 2012;Eveland & Scheufele, 2000;Gaziano, 2010;Hwang & Jeong, 2009;Ksiazek et al, 2010;Strömbäck et al, 2013;Wei & Hindman, 2011). Thus, the concern is rooted in how changes in the supply of news and other political information influence the demand and, subsequently, learning about politics and current affairs.…”
Section: Concern 6: Towards Increasing Inequalitiesmentioning
confidence: 99%
“…Research has shown that individual media content preferences have become increasingly important as a predictor of news consumption and learning during the gradual shift from a low-choice to a high-choice media environment (Prior, 2005(Prior, , 2007Strömbäck, Djerf-Pierre, & Shehata, 2013). As noted by Prior (2005), "As media choice increases, content preferences .…”
mentioning
confidence: 99%
“…Factoring in that other research has shown that the framing of politics as a strategic game also leads to decreasing political interest (Shehata, 2014), one of the most important predictors of news media consumption (Strö mbäck & Shehata, 2010), the media may undermine not only trust in 18 HOPMANN, SHEHATA, STRÖ MBÄ CK politics and the media but also the foundation on which their appeal to people relies. This change is particularly noteworthy, as the transformation from low-choice to high-choice media environments (Prior, 2007) has made political interest an even more important predictor of news media consumption (Strö mbäck, Djerf-Pierre, & Shehata, 2013). By framing politics as a strategic game and thereby undermining trust not only in politics but also in the media, the media may thus simultaneously weaken the incentives for people to follow the news in mainstream media and strengthen the incentives for people to turn to alternative news sources.…”
Section: Discussionmentioning
confidence: 99%